When professional opinion is not enough. Issue 7598 (19th April 2007) - Treasure, Tom; Utley, Martin; Hunt, Ian
Abstract : Surgical resection of pulmonary metastases in patients with colorectal cancer is common practice, but Tom Treasure, Martin Utley, and Ian Hunt question the strength of evidence behind advice from NICE